Extraction of condensed tannin in cocoa powder by using different ratio of solvent (acetone:water) / Siti Hawa Khairudin - Khairudin, Siti Hawa (Faculty of Applied Sciences, 2009)
Condensed Tannin (CT) is a water-soluble phenolic compound. CT also known as Proanthocyanidins (PAs) are oligomers and polymers of flavan-3-ol units. This compound comprise from a group of polyhydroxyflavan-3-ol oligomers and polymers linked by carbon-carbon bond between flavanol subunit. The function of CT in foods is as astringency. CT also are able to interact with biological systems or physiological effects, such as antioxidant, anti-allergy, anti-hypertensive, as well as antimicrobial activities. There is a limit of condensed tannin in human body which is not exceeding than 6% of human body weight. If do so, it will cause an anemia and precipitation in body when CT interact with enzyme and iron in body. For this study, acid-butanol method was used for analysis before determining the condensed tannin by using UV/VIS spectrophotometry instrument. For the extraction, two ratio of acetone was used for immersing the cocoa powder for 2 days. The ratio of solvent use is 70% and 80%. There have 3 samples labelled as sample A, sample B and sample C as shown in Appendix E was used for comparison. As results, sample A give the higher amount of CT followed by sample B and sample C. for the comparison of solvent ratio, 70% acetone give the higher extraction of CT compared with 80% acetone.